A comparative study of food consumption patterns among children younger than three in Russia and Vietnam - N.A. Lebedeva-Nesevrya; Le Thi Hong Hao; A.O. Barg; Tran Cao Son; Bui Quang Dong; Vu Ngoc Tu; D.V. Suvorov (Analiz Riska Zdorovʹû, 2019)
The publication presents the results of the exposure assessment within the framework of a joint Russian-Vietnamese study aimed at children’s health risk assessment associated with the N-nitrosamines contamination in food. People who permanently cared for children aged from six months to three years were questioned in two urbanized areas of Vietnam and Russia – in the cities of Hanoi (n=481) and Perm (n=183). It is shown that the structure of food consumption among children up to three years differs significantly. Children’s nutrition in Russia is includes a lot of dry soluble cereals and canned meat/vegetables. The most common product in children's nutrition in Vietnam has no analogues in Russia: it is purchased cereals prepared in specialized stores. Canned foods and dry soluble cereals are also included in the diet of children in Vietnam, but the share of consumers and consumption volumes for them are significantly lower than in Russia. Thus, in the age group of 6–12 months, the share of consumers in Russia is 53 %, in Vietnam – 21 %, the median distribution of average daily consumption in Russia is 152 grams, in Vietnam – 28 grams. Taking into account the share of consumers, as well as the volume and frequency of consumption, we determined the priority products for the children’s health risk assessment associated with the N-nitrosamines contamination in food. They are canned meat and dry soluble cereals in Russia; grilled meat and sausages; in Vietnam.